Strategic Intelligence and its Role in Achieving Outstanding Performance - Hadi, Jalal Fahem; Salim, Shukri (جامعة الكوفة - كلية الإدارة والاقتصاد, 2023)
يهدف هذا البحث إلى التعرف على واقع الذكاء الاستراتيجي في المؤسسة الأمنية ومعرفة مدى تأثيره على الأداء المتميز، وذلك من خلال متغيرات البحث ليكون إطارا مفاهيميا يتمثل في (الذكاء الاستراتيجي ودوره في تحقيق الأداء المتميز). وذلك من خلال دراسة استطلاعية لقيادة شرطة محافظة النجف التابعة لوزارة الداخلية العراقية، والتي أسفرت عن الزيارات الميدانية التي قام بها الباحث للتعرف على المشاكل التي تعاني منها المؤسسة الأمنية أثناء أداء عمله وخاصة حول تنفيذ الخطط الميدانية والإدارية. يهدف هذا البحث إلى التعرف على أثر الذكاء الاستراتيجي في تحقيق الأداء المتميز. ركزت الدراسة على عينة من العاملين في المؤسسة الأمنية، سعيا لتحقيق الأهداف. يتكون مجتمع الدراسة من (1365) وعدد الاستبانات الموزعة (325) وعدد الاستبيانات المستردة (316). أما بالنسبة لعدد الاستبيانات المستبعدة وغير الصالحة (14) فقد أصبح عدد الاستمارات الصالحة للتحليل الإحصائي (302). تم تصميم الاستبيان بناء على عدة معايير دولية رصينة، بأبعاد الذكاء الاستراتيجي (الاستشراف، الرؤية، الشراكة، التفكير التنظيمي، التحفيز) ومتغير الأداء المتميز المتمثل في (القيادة، الموارد البشرية، العمليات، رضا العملاء، الثقافة التنظيمية) للوصول إلى نتائج تنموية. This research aims to identify the reality of strategic intelligence in the security institution and to know the extent of its impact on outstanding performance, through research variables to be a conceptual framework represented by (strategic intelligence and its role in achieving outstanding performance). This was done through an exploratory study of the Najaf Governorate Police Command affiliated with the Iraqi Ministry of Interior, which resulted in the field visits carried out by the researcher to identify the problems that the security institution suffers from during the performance of his work, especially about the implementation of field and administrative plans. This research aims to identify the impact of strategic intelligence in achieving outstanding performance. The study focused on a sample of workers in the security establishment, in pursuit of the objectives. The study population consists of (1365) and the number of distributed questionnaires was (325) and the number of questionnaires retrieved (was 316). As for the number of excluded and invalid questionnaires (14), here the number of valid forms for statistical analysis became (302). The questionnaire was designed based on several solid international standards, with the dimensions of strategic intelligence (foreseeing, vision, partnership, organizational thinking, motivation) and the outstanding performance variable representing (leadership, human resources, operations, customer satisfaction, and organizational culture), to reach developmental outcomes.
Keywords: القيادات الإدارية -- التفكير الاستراتيجي -- الثقافة التنظيمية -- رضا العملاء